2019
DOI: 10.11594/jk6em.02.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Academic Supervision and School Culture on Teacher’s Teaching Quality in Public Islamic Senior High School Banjarmasin

Abstract: The research aimed at analyzing the effect of school principals' academic supervision, the effect of school culture and the effect of both of them the simultaneous influence of both on the teacher teaching quality in all MAN at Banjarmasin city is conducted through quantitative methods. Statistical data shows 93.90% of teachers believe that the school principal has implemented supervision well. 99.40% believe that the school culture encourages the existence of good teaching quality and 99.95% believe that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This qualitative study used case-study and descriptive methods because the problems discussed are currently happening (actually) (Sudarjat et al, 2015). The data obtained were processed from data collection to drawing conclusions so as to give a clear description on the management of teacher competency development and training in improving learning quality (Suriansyah & Effendi, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study used case-study and descriptive methods because the problems discussed are currently happening (actually) (Sudarjat et al, 2015). The data obtained were processed from data collection to drawing conclusions so as to give a clear description on the management of teacher competency development and training in improving learning quality (Suriansyah & Effendi, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Mutohar and Trisnantari (2020) stated that academic supervision simultaneously with managerial capabilities and school organizational culture can enhance teacher performance and further enhance madrasas' effectiveness. Finally, (Rachman, 2020;Mujiyati, Suriansyah and Effendi, 2019) found that academic supervision can improve teachers' quality in teaching.…”
Section: H5 Academic Supervision Positively Affects Teaching Competence H6 Academic Supervision Positively Affects Teacher Performance H7mentioning
confidence: 99%
“…The academic supervision directly affects the state of the teacher's behavioral environment in classroom management in the learning process with the teacher directly or indirectly changing his mind by providing teaching materials in preparation, core and completion activities (Alwis et al, 2020;Suriansyah & Effendi, 2019;Wichmann-Hansen et al, 2015). The skill and ability to change mind can be seen at the learning stage (Sitaasih, 2020;Usman, 2018).…”
Section: Introductionmentioning
confidence: 99%